High voltage resistant electrolyte, preparation method and sodium ion battery

By using specific composite additives in the electrolyte of sodium ion battery, the electrolyte group distribution ratio is optimized to form a stable SEI film and CEI film, the problem of unstable ether electrolyte at high pressure is solved, and a sodium ion battery with high energy density and long life is achieved.

CN118630317BActive Publication Date: 2025-03-21CHINA SODA ENERGY (YANGZHOU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411102716.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2025-03-21
Estimated Expiration
2044-08-13

AI Technical Summary

Technical Problem

The ether electrolyte of sodium ion batteries is unstable under high pressure, resulting in electrolyte decomposition and CEI film deterioration, limiting the high energy density and cycling performance of the battery.

Method used

By optimizing the ratio of each component in the electrolyte, a composite additive composed of sodium nitrate, sodium difluoroxalic acid borate, tris(trimethylsilicon)phosphite, vinyl carbonate, fluorovinyl carbonate and 1,3-propane sulfonate lactone is used to form a stable SEI film and CEI film to improve the ionic conductivity and stability of the electrolyte.

Benefits of technology

It realizes high energy density and high stability of sodium ion batteries at high voltages, improves circulation performance and rate performance, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118630317B_ABST
    Figure CN118630317B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of sodium ion batteries, and provides a high-voltage resistant electrolyte and a preparation method and a sodium ion battery, wherein the high-voltage resistant electrolyte includes a conductive sodium salt, an organic solvent and a composite additive; wherein the conductive sodium salt is sodium hexafluorophosphate, the organic solvent is diethylene glycol dimethyl ether, and the composite additive is sodium nitrate, sodium difluorooxalatoborate, tris(trimethylsilyl)phosphite, vinylene carbonate, fluoroethylene carbonate and 1,3-propane sultone. The present invention optimizes the ratio of each component in the electrode liquid, and under the joint action of a multi-component additive, the electrolyte system has both high energy density and high stability, which is conducive to meeting the requirements of sodium ion batteries for cycle performance and rate performance at high voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries and relates to a high-voltage resistant electrolyte and a preparation method thereof and a sodium ion battery. Background Art

[0002] New energy systems represented by lithium-ion batteries are considered to be one of the most promising options to replace traditional fossil energy, but as the market share increases, the development of new ion battery systems to replace lithium-ion batteries is of great significance.

[0003] Sodium-ion batteries are considered to be one of the most promising alternatives due to their similar properties to lithium and abundant natural reserves, and have therefore been increasingly studied. However, the development experience of lithium-ion batteries cannot fully adapt to sodium-ion batteries, especially in the development of electrolytes. The sodium-ion battery ester electrolyte with a similar formula configured according to the traditional lithium-ion ester electrolyte has encountered problems such as incompatibility with traditional graphite negative electrodes, low coulombic efficiency in the first week, and large polarization of the electrochemical system. Therefore, the research on new electrolytes and other key materials is an indispensable part of the industrialization process of sodium-ion batteries.

[0004] Ether electrolytes have excellent negative electrode interface modification effects. They can form thinner and denser SEI films at the negative electrode, which significantly improves the first-cycle coulomb efficiency and interface kinetics of the negative electrode. At the same time, ether electrolytes can exert the energy storage capacity of graphite in sodium-ion batteries through the solvent co-intercalation process. However, these advantages are limited to the development of negative electrode materials for sodium-ion batteries. However, the antioxidant capacity of ether electrolytes is weak, which causes the electrolyte to decompose in large quantities and the CEI film to continue to deteriorate when matched with high-voltage positive electrodes, causing the battery system to fail quickly. Therefore, the high voltage instability of ether electrolytes makes it difficult to be compatible with common sodium-ion battery positive electrode materials, limiting its voltage window and application in high-energy-density sodium-ion batteries. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-voltage resistant electrolyte, a preparation method and a sodium ion battery. The present invention optimizes the ratio of the components in the electrode liquid, and under the joint action of a multi-component additive, the electrolyte system has both high energy density and high stability, which is conducive to meeting the requirements of sodium ion batteries for cycle performance and rate performance at high voltage.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a high-voltage resistant electrolyte, comprising a conductive sodium salt, an organic solvent and a composite additive; wherein the conductive sodium salt is sodium hexafluorophosphate, the organic solvent is diethylene glycol dimethyl ether, and the composite additive is sodium nitrate, sodium difluorooxalatoborate, tris(trimethylsilyl)phosphite, vinylene carbonate, fluoroethylene carbonate and 1,3-propane sultone.

[0008] The present invention adopts a composite additive composed of sodium nitrate, sodium difluorooxalatoborate, tris(trimethylsilyl)phosphite, vinylene carbonate, fluoroethylene carbonate and 1,3-propane sultone, which effectively reduces the viscosity of the high-voltage electrolyte, improves the ionic conductivity of the high-voltage electrolyte, is conducive to the formation of a stable, uniform, dense CEI film / SEI film with certain toughness and rigidity between the high-voltage electrolyte and the positive and negative electrode materials at the solid-liquid interphase layer, can effectively inhibit the occurrence of side reactions of organic solvents on the surfaces of the positive and negative electrode sheets, and improves the compatibility of the electrolyte with the positive and negative electrode materials; in addition, the present invention optimizes the ratio of each component in the electrode liquid, and under the joint action of the multi-component additives, the electrolyte system has both high energy density and high stability, which is conducive to meeting the requirements of sodium ion batteries for cycle performance and rate performance at high voltage.

[0009] On the one hand, the SEI film formed by the high-voltage electrolyte provided by the present invention during the charge and discharge process of the sodium ion battery has a good ion transmission rate, which promotes the solvation of Na + The desolvation reduces the carrier transmission energy barrier in the SEI film, ensuring the rapid dynamic process of the battery system; at the same time, the formed SEI film has good electronic insulation, controls the range of electron tunneling, and prevents the continuous thickening of the interface layer caused by the continuous decomposition of the electrolyte, resulting in irreversible capacity loss and continuous increase of the interface impedance of the battery system; on the other hand, the SEI film formed by the high-voltage resistant electrolyte provided by the present invention has certain toughness and stiffness. The improvement of toughness can prevent the local rupture and failure of the SEI film due to the volume change of the positive and negative electrode materials during the embedding / de-embedding process of sodium ions, resulting in the continuous growth of the new interface layer and the continuous progress of side reactions; the improvement of stiffness can provide certain support and protection for the drastic volume expansion of certain positive and negative electrode materials during the charging and discharging process.

[0010] During the initial charge and discharge, an inevitable side reaction occurs between the electrode and the electrolyte. In essence, the rise and fall of the Fermi level of the electrode charge and discharge state exceeds the stability window of the electrolyte, thereby driving the directional transfer of electrons, and then inducing a redox reaction between the electrolyte and the electrode. During the positive electrode charging process, as the sodium ions are released, the Fermi level of the sodium-poor positive electrode gradually decreases. When it decreases below the highest occupied orbital (HOMO level) of the electrolyte component, it will induce the transfer of electrons in the liquid phase to the bulk phase, causing the electrolyte component to lose electrons and undergo an oxidation reaction. The product of the oxidation reaction is deposited on the surface of the positive electrode according to different reaction sequences according to the HOMO energy level to form a CEI film. Similarly, the formation of the SEI film is due to the gradual increase in the Fermi level of the sodium-embedded negative electrode. When it rises above the lowest unoccupied orbital (LUMO level) of the electrolyte component, the electrons at the negative electrode will spontaneously flow to the empty orbitals of the electrolyte components, causing the electrolyte components to gain electrons and undergo a reduction reaction. The products of the reduction reaction are deposited on the surface of the negative electrode according to different reaction sequences based on the LUMO energy level to form the SEI film. This reduction and oxidation process will continue until the passivation effect of the CEI film and the SEI film can completely shield electron conduction.

[0011] The solid-liquid interface between the electrode and the electrolyte has a double-layer structure. The inner layer near the electrode is composed of inorganic compounds that preferentially react and dissociate. Its structure is tight and can block the electron tunneling path. It mainly plays the role of ion conduction and electronic insulation, thereby achieving the purpose of widening the high-voltage stability window of the electrolyte; while the outer layer near the electrolyte is composed of loose organic compounds with large pores, and the outer layer morphology will undergo continuous reforming and evolution during the cycle. The present invention is based on the double-layer structure and solvation theory. By optimizing the ratio of various additives in the electrolyte, the interface structure of the electrode and the electrolyte is adjusted in situ, which can effectively optimize the interface quality and obtain SEI membranes and CEI membranes with ideal morphology, thereby significantly improving the electrochemical performance of sodium ion batteries. The difficulty of the present invention lies in the diversity of the selection of additive components and how to determine the appropriate amount of additives to find a balance among various electrochemical properties, so as to design the optimal electrolyte formula. Based on this, the present invention particularly prefers sodium nitrate, sodium difluorooxalatoborate, tris(trimethylsilyl)phosphite, vinylene carbonate, fluoroethylene carbonate and 1,3-propane sultone among many types of additives. After the above additives are compounded in a certain proportion, they can not only independently improve the electrochemical properties of sodium ion batteries, but also have a synergistic effect with each other.

[0012] The present invention adds a small amount of sodium nitrate to the electrolyte. The addition of sodium nitrate has a significant regulating effect on the morphology, structure and composition of the CEI membrane. On the one hand, due to NO3 -The HOMO energy level of sodium nitrate is -0.49eV, which is much higher than other components in the electrolyte. Therefore, sodium nitrate has a strong tendency to decompose preferentially and can be used as an ideal sacrificial agent and film-forming agent. On the other hand, adding a very small amount of NO3 - The primary solvation structure of sodium ions was regulated, and an electrode-electrolyte interface with stronger protective ability was induced. A CEI film rich in Na3N / NaF was in situ generated at the solid-liquid interface between the positive electrode plate and the electrolyte. The generated CEI film has stronger protective ability and can protect diethylene glycol dimethyl ether, which is most easily oxidized and decomposed, thereby effectively inhibiting the decomposition of diethylene glycol dimethyl ether on the positive electrode side during charging, significantly improving the high-voltage stability of the electrolyte, and increasing the voltage tolerance window of the electrolyte, so that it can also obtain stable rate performance and cycle performance under the high voltage window of 2.5~4V.

[0013] When sodium nitrate is not added, diethylene glycol dimethyl ether is oxidized and decomposed to produce Na2CO3 with poor electronic insulation and poor compactness. Na2CO3 gradually accumulates in the inner layer, resulting in poor insulation and compactness of the generated CEI film, which cannot effectively protect the electrolyte, resulting in continuous deterioration of the interface and continuous oxidation of the electrolyte. After adding sodium nitrate, due to NO3 - The number of electron donors is much higher than that of hexafluorophosphate ions. Its strong electron-donating ability weakens the restriction of the overall solvation structure on sodium ions, so it can enter the inner solvation structure more easily. - Entering the inner solvation structure, some of the hexafluorophosphate ions in the solvation structure are dissociated. In the competition process, the dissociated hexafluorophosphate ions and some NO3 - It is preferentially adsorbed in the inner layer and becomes the component that is preferentially decomposed in the early stage of CEI membrane formation. When the electrochemistry is started, the preferentially adsorbed hexafluorophosphate ions in the electrolyte decompose, and at the same time, NO3 - The solvated clusters of NO3 decompose preferentially at the interface, providing N-containing dominant components for the formation of CEI films. - The synergistic decomposition with hexafluorophosphate ions produces a dense CEI film mainly composed of Na3N, NaF and Na2O, which has a strong inhibitory effect on electron tunneling, thereby reducing the continuous growth of the interface and the continuous decomposition of the electrolyte.

[0014] The present invention adds fluoroethylene carbonate to the high-voltage electrolyte. Since it has a lower highest occupied molecular orbital and a higher oxidation decomposition potential, it is difficult for oxidation reaction to occur on the positive electrode, which can protect the positive electrode material to a certain extent. In addition, since fluoroethylene carbonate has an obvious low decomposition barrier and fluorine atoms have a strong electron-withdrawing effect, fluoroethylene carbonate can be preferentially reduced and decomposed on the negative electrode surface at a higher potential to generate a NaF-rich SEI film. The NaF-rich SEI film has higher interface energy and mechanical strength, which can effectively inhibit the growth of sodium dendrites and greatly prolong the cycle performance of the sodium ion battery. At the same time, fluoroethylene carbonate can also uniformly orient the organic solvent molecules on the negative electrode interface, so that the organic solvent molecules are rearranged on the negative electrode surface, which is conducive to the formation of a dense, uniform and stable SEI film, which can effectively reduce the internal resistance of the sodium ion battery and improve the cycle performance of the sodium ion battery. However, the higher NaF + The diffusion barrier will hinder the Na + The diffusion of fluoroethylene carbonate is slow, especially at low temperatures, and the polarization increases significantly. In addition, due to the presence of trace water in the electrolyte, fluoroethylene carbonate will inevitably hydrolyze to generate harmful substances such as hydrofluoric acid gas, thereby deteriorating the interface between the electrode and the electrolyte and aggravating the occurrence of side reactions.

[0015] In order to avoid excessive production of NaF and the impact of Na + In order to prevent the diffusion of sodium ion batteries, the present invention particularly adds tris(trimethylsilyl)phosphite to the high-voltage resistant electrolyte, which helps to improve the cycle stability and capacity retention rate of sodium ion batteries under high temperature conditions, and also eliminates the influence of self-discharge. This is because, on the one hand, during the charge and discharge process, the phosphorus and silicon elements in tri(trimethylsilyl)phosphite derive additional cross-linking sites, which can effectively inhibit the formation of soluble oligomers and ensure the integrity of the organic components of the interface film; in addition, tri(trimethylsilyl)phosphite has a higher HOMO energy level, which can quickly passivate the surface of the active material and reduce the initial battery polarization, so that the sodium ion battery has excellent electrochemical performance; on the other hand, there is a synergistic effect between tri(trimethylsilyl)phosphite and fluoroethylene carbonate. This is because the Si-O functional group in tri(trimethylsilyl)phosphite can be used as a hydrofluoric acid scavenger in the electrolyte to quickly remove harmful substances such as hydrofluoric acid gas produced by the hydrolysis of fluoroethylene carbonate, thereby controlling the amount of NaF generated to a certain extent, and balancing the ratio of organic and inorganic components in the SEI film on the basis of reducing the hydrofluoric acid content, and finally generating a low-solubility, dense and thin SEI film, which effectively reduces the Na content of the SEI film. + Diffusion barrier.

[0016] The present invention adds sodium difluoro oxalate borate as a film-forming additive in the high-voltage electrolyte, and a uniform inorganic-rich CEI film and SEI film with high ionic conductivity can be formed on the positive and negative electrode surfaces, significantly improving the cycle performance of sodium ion batteries. In addition, there is also a synergistic effect between sodium difluoro oxalate borate and tris (trimethylsilyl) phosphite, and tris (trimethylsilyl) phosphite can effectively eliminate the fluorine ions in the reduction product of sodium difluoro oxalate borate, and can react with hydrofluoric acid to form a stronger Si-F bond, not only building a stable and firm SEI film, but also being able to effectively suppress the volume expansion of active materials. In addition, when only sodium difluoro oxalate borate is added, the interface impedance is significantly increased, and after adding tris (trimethylsilyl) phosphite and sodium difluoro oxalate borate, the interface impedance is significantly reduced.

[0017] The present invention adds vinylene carbonate to the high-voltage electrolyte, which can also produce a synergistic effect with fluoroethylene carbonate, so that the irreversible capacity loss of the sodium ion battery during the first cycle is reduced. This is because the SEI film formed by vinylene carbonate and fluoroethylene carbonate on the surface of the pole piece is decomposed before the organic solvent, reducing the reaction of the organic solvent on the pole piece; at the same time, the decomposition of vinylene carbonate and fluoroethylene carbonate on the pole piece is relatively mild, and there is no violent decomposition of organic solvents. In addition, when vinylene carbonate participates in the solvation structure of sodium ions, it reduces the LUMO energy level of the electrolyte, thereby effectively slowing down the decomposition of the organic solvent, maintaining the rapid dynamics of sodium ions, and realizing a long-lasting charge and discharge process. However, the presence of vinylene carbonate will cause the sodium ion battery to generate a large amount of carbon dioxide gas during the charge and discharge process. For this reason, the present invention adds 1,3-propane sultone to the high-voltage electrolyte. When 1,3-propane sultone is not added, the presence of vinylene carbonate will cause the sodium ion battery to generate a large amount of carbon dioxide gas during the charge and discharge process. After adding 1,3-propane sultone to the electrolyte, the gas production caused by vinylene carbonate can be effectively suppressed. In addition, the addition of 1,3-propane sultone will greatly improve the capacity retention rate of the sodium ion battery. This is because the decomposition of 1,3-propane sultone will form sulfates and sulfites, which can stabilize the SEI film, thereby obtaining a high-performance, long-life sodium ion battery.

[0018] As a preferred technical solution of the present invention, the concentration of sodium hexafluorophosphate in the high-voltage resistant electrolyte is 0.8~1.2mol / L, for example, it can be 0.8mol / L, 0.85mol / L, 0.9mol / L, 0.95mol / L, 1mol / L, 1.05mol / L, 1.1mol / L, 1.15mol / L or 1.2mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] As a preferred technical solution of the present invention, the molar concentration of sodium nitrate in the high-voltage resistant electrolyte is 0.08~0.12mol / L, for example, it can be 0.08mol / L, 0.085mol / L, 0.09mol / L, 0.095mol / L, 0.1mol / L, 0.105mol / L, 0.11mol / L, 0.115mol / L or 0.12mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] As a preferred technical solution of the present invention, the mass fraction of sodium difluorooxalatoborate in the high-voltage resistant electrolyte is 0.4~0.6wt%, for example, it can be 0.4wt%, 0.42wt%, 0.44wt%, 0.46wt%, 0.48wt%, 0.5wt%, 0.52wt%, 0.54wt%, 0.56wt%, 0.58wt% or 0.6wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] As a preferred technical solution of the present invention, the mass fraction of tris(trimethylsilyl)phosphite in the high-voltage electrolyte is 0.5~1.5wt%, for example, it can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt% or 1.5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] As a preferred technical solution of the present invention, the mass fraction of vinylene carbonate in the high-voltage resistant electrolyte is 2.5~3.5wt%, for example, it can be 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3.0wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt% or 3.5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] The present invention specifically limits the mass fraction of vinylene carbonate in the high-voltage resistant electrolyte to 2.5~3.5wt%. When the addition amount of vinylene carbonate exceeds 3.5wt%, it will lead to increased polarization of the sodium ion battery and deterioration of the cycle performance of the sodium ion battery. In addition, the double bonds in the structure of vinylene carbonate make it extremely easy to be oxidized at low voltage. When excessive addition is added, it will lead to an increase in the thickness of the SEI film, resulting in an increase in the internal resistance of the sodium ion battery.

[0024] As a preferred technical solution of the present invention, the mass fraction of fluoroethylene carbonate in the high-voltage resistant electrolyte is 4.5~5.5wt%, for example, it can be 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt%, 5.0wt%, 5.1wt%, 5.2wt%, 5.3wt%, 5.4wt% or 5.5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] The present invention specifically limits the mass fraction of fluoroethylene carbonate to 4.5-5.5wt%. When fluoroethylene carbonate is added to the high-voltage resistant electrolyte, the cycle performance of the sodium ion battery is significantly improved. However, the higher the amount of fluoroethylene carbonate added, the better. When the amount of fluoroethylene carbonate added exceeds 4.5wt%, the viscosity coefficient of the electrolyte will increase, resulting in obstruction of sodium ion migration and affecting the charge and discharge performance of the sodium ion battery. In addition, too high an addition amount will cause fluoroethylene carbonate to react with the electrode, making the structure of the SEI film unstable, resulting in uneven sodium deposition and increased interface resistance.

[0026] As a preferred technical solution of the present invention, the mass fraction of 1,3-propane sultone in the high-voltage resistant electrolyte is 1.5~2.5wt%, for example, it can be 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt% or 2.5wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] 1,3-Propane sultone has excellent effects in inhibiting gas production on the negative electrode surface and improving cycle performance, but the addition amount of 1,3-propane sultone should not be too high. The present invention specifically limits the mass fraction of 1,3-propane sultone in the high-voltage resistant electrolyte to 1.5~2.5wt%. When the addition amount of 1,3-propane sultone exceeds 2.5wt%, the negative electrode impedance will increase significantly, which has a greater impact on the rate performance and charge and discharge performance of the sodium ion battery.

[0028] In a second aspect, the present invention provides a method for preparing the high-voltage resistant electrolyte according to the first aspect, the preparation method comprising:

[0029] In a glove box with an argon atmosphere, sodium nitrate, sodium difluorooxalatoborate, tris(trimethylsilyl)phosphite, vinylene carbonate, fluoroethylene carbonate and 1,3-propane sultone are added to diethylene glycol dimethyl ether and mixed evenly, and then molecular sieves are added to remove water and purify to obtain a mixed solution; sodium hexafluorophosphate is added to the mixed solution, and the high-voltage resistant electrolyte is obtained after mixing evenly.

[0030] In a third aspect, the present invention provides a sodium ion battery comprising the high-voltage resistant electrolyte described in the first aspect, the sodium ion battery comprising an outer shell and a battery cell located inside the outer shell, the high-voltage resistant electrolyte is injected into the outer shell, the battery cell is immersed in the high-voltage resistant electrolyte, and the battery cell comprises a positive electrode sheet, a separator and a negative electrode sheet stacked in sequence.

[0031] The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector. The positive electrode active material layer comprises a positive electrode active material, a conductive agent and a binder. The positive electrode active material is sodium vanadium phosphate.

[0032] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector. The negative electrode active material layer comprises a negative electrode active material, a conductive agent and a binder. The negative electrode active material is hard carbon.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The present invention adopts a composite additive composed of sodium nitrate, sodium difluorooxalatoborate, tris(trimethylsilyl)phosphite, vinylene carbonate, fluoroethylene carbonate and 1,3-propane sultone, which effectively reduces the viscosity of the high-voltage electrolyte, improves the ionic conductivity of the high-voltage electrolyte, is conducive to the formation of a stable, uniform, dense CEI film / SEI film with certain toughness and rigidity between the high-voltage electrolyte and the positive and negative electrode materials at the solid-liquid interphase layer, can effectively inhibit the occurrence of side reactions of organic solvents on the surfaces of the positive and negative electrode sheets, and improves the compatibility of the electrolyte with the positive and negative electrode materials; in addition, the present invention optimizes the ratio of each component in the electrode liquid, and under the joint action of the multi-component additives, the electrolyte system has both high energy density and high stability, which is conducive to meeting the requirements of sodium ion batteries for cycle performance and rate performance at high voltage. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a rate performance test diagram of button cells assembled from Example 1 of the present invention and Comparative Example 7;

[0036] Figure 2 The first cycle cyclic voltammetry curve of the button cell assembled with the high voltage resistant electrolyte provided in Example 1 of the present invention and Comparative Example 13;

[0037] Figure 3 Electrochemical impedance diagrams of button cells assembled with the high-voltage electrolyte provided in Example 1 of the present invention after the 5th, 10th, 25th and 50th cycles;

[0038] Figure 4Electrochemical impedance diagrams of button-type batteries assembled with the high-voltage resistant electrolyte provided in Comparative Example 13 of the present invention after the 5th, 10th, 25th and 50th cycles. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0040] The chemical reagents used in the specific implementation are all commercially available products, and their specifications, batch numbers, manufacturers and other information are as follows:

[0041] Sodium hexafluorophosphate: S70602-5g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0042] Diethylene glycol dimethyl ether: B65650-1ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0043] Sodium nitrate: purity>99%, purchased from Hubei Xinyinghe Chemical Co., Ltd.;

[0044] Sodium difluorooxalatoborate: A517304, purchased from Zhengzhou Huiju Chemical Co., Ltd.;

[0045] Tris(trimethylsilyl)phosphite: purity>99%, purchased from Wuhan Haorong Biotechnology Co., Ltd.;

[0046] Vinylene carbonate: purity>98%, purchased from Kangdisi Chemical (Hubei) Co., Ltd.;

[0047] Fluoroethylene carbonate: S70142-25g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0048] 1,3-Propane sultone: purity>99%, Chongqing Ruiya Biotechnology Co., Ltd.

[0049] Example 1

[0050] This embodiment provides a high-voltage resistant electrolyte, which includes a conductive sodium salt, an organic solvent and a composite additive.

[0051] The conductive sodium salt is sodium hexafluorophosphate, and the concentration of sodium hexafluorophosphate in the high-voltage electrolyte is 0.8 mol / L.

[0052] The organic solvent is diethylene glycol dimethyl ether.

[0053] The composite additive consists of sodium nitrate, sodium difluorooxalatoborate, tris(trimethylsilyl)phosphite, vinylene carbonate, fluoroethylene carbonate and 1,3-propane sultone, wherein the molar concentration of sodium nitrate is 0.08 mol / L, the mass fraction of sodium difluorooxalatoborate is 0.4 wt %, the mass fraction of tris(trimethylsilyl)phosphite is 0.5 wt %, the mass fraction of vinylene carbonate is 2.5 wt %, the mass fraction of fluoroethylene carbonate is 4.5 wt %, and the mass fraction of 1,3-propane sultone is 1.5 wt %.

[0054] Example 2

[0055] This embodiment provides a high-voltage resistant electrolyte, which includes a conductive sodium salt, an organic solvent and a composite additive.

[0056] The conductive sodium salt is sodium hexafluorophosphate, and the concentration of sodium hexafluorophosphate in the high-voltage electrolyte is 0.9 mol / L.

[0057] The organic solvent is diethylene glycol dimethyl ether.

[0058] The composite additive consists of sodium nitrate, sodium difluorooxalatoborate, tris(trimethylsilyl)phosphite, vinylene carbonate, fluoroethylene carbonate and 1,3-propane sultone, wherein the molar concentration of sodium nitrate is 0.09 mol / L, the mass fraction of sodium difluorooxalatoborate is 0.45 wt %, the mass fraction of tris(trimethylsilyl)phosphite is 0.8 wt %, the mass fraction of vinylene carbonate is 2.8 wt %, the mass fraction of fluoroethylene carbonate is 4.8 wt %, and the mass fraction of 1,3-propane sultone is 1.8 wt %.

[0059] Example 3

[0060] This embodiment provides a high-voltage resistant electrolyte, which includes a conductive sodium salt, an organic solvent and a composite additive.

[0061] The conductive sodium salt is sodium hexafluorophosphate, and the concentration of sodium hexafluorophosphate in the high-voltage electrolyte is 1 mol / L.

[0062] The organic solvent is diethylene glycol dimethyl ether.

[0063] The composite additive consists of sodium nitrate, sodium difluorooxalatoborate, tri(trimethylsilyl)phosphite, vinylene carbonate, fluoroethylene carbonate and 1,3-propane sultone, wherein the molar concentration of sodium nitrate is 0.1 mol / L, the mass fraction of sodium difluorooxalatoborate is 0.5 wt %, the mass fraction of tri(trimethylsilyl)phosphite is 1 wt %, the mass fraction of vinylene carbonate is 3 wt %, the mass fraction of fluoroethylene carbonate is 5 wt %, and the mass fraction of 1,3-propane sultone is 2 wt %.

[0064] Example 4

[0065] This embodiment provides a high-voltage resistant electrolyte, which includes a conductive sodium salt, an organic solvent and a composite additive.

[0066] The conductive sodium salt is sodium hexafluorophosphate, and the concentration of sodium hexafluorophosphate in the high-voltage electrolyte is 1.1 mol / L.

[0067] The organic solvent is diethylene glycol dimethyl ether.

[0068] The composite additive consists of sodium nitrate, sodium difluorooxalatoborate, tri(trimethylsilyl)phosphite, vinylene carbonate, fluoroethylene carbonate and 1,3-propane sultone, wherein the molar concentration of sodium nitrate is 0.11 mol / L, the mass fraction of sodium difluorooxalatoborate is 0.55 wt %, the mass fraction of tri(trimethylsilyl)phosphite is 1.2 wt %, the mass fraction of vinylene carbonate is 3.2 wt %, the mass fraction of fluoroethylene carbonate is 5.2 wt %, and the mass fraction of 1,3-propane sultone is 2.2 wt %.

[0069] Example 5

[0070] This embodiment provides a high-voltage resistant electrolyte, which includes a conductive sodium salt, an organic solvent and a composite additive.

[0071] The conductive sodium salt is sodium hexafluorophosphate, and the concentration of sodium hexafluorophosphate in the high-voltage electrolyte is 1.2 mol / L.

[0072] The organic solvent is diethylene glycol dimethyl ether.

[0073] The composite additive consists of sodium nitrate, sodium difluorooxalatoborate, tri(trimethylsilyl)phosphite, vinylene carbonate, fluoroethylene carbonate and 1,3-propane sultone, wherein the molar concentration of sodium nitrate is 0.12 mol / L, the mass fraction of sodium difluorooxalatoborate is 0.6 wt %, the mass fraction of tri(trimethylsilyl)phosphite is 1.5 wt %, the mass fraction of vinylene carbonate is 3.5 wt %, the mass fraction of fluoroethylene carbonate is 5.5 wt %, and the mass fraction of 1,3-propane sultone is 2.5 wt %.

[0074] Comparative Example 1

[0075] This comparative example provides a high-voltage resistant electrolyte, which is different from Example 1 in that the mass fraction of vinylene carbonate is adjusted to 2wt%, and the contents and proportions of other components are exactly the same as those in Example 1.

[0076] Comparative Example 2

[0077] This comparative example provides a high-voltage resistant electrolyte, which is different from Example 1 in that the mass fraction of vinylene carbonate is adjusted to 4wt%, and the contents and proportions of other components are exactly the same as those in Example 1.

[0078] Comparative Example 3

[0079] This comparative example provides a high-voltage resistant electrolyte, which is different from Example 1 in that the mass fraction of fluoroethylene carbonate is adjusted to 4wt%, and the contents and proportions of other components are exactly the same as those in Example 1.

[0080] Comparative Example 4

[0081] This comparative example provides a high-voltage resistant electrolyte, which is different from Example 1 in that the mass fraction of fluoroethylene carbonate is adjusted to 6wt%, and the contents and proportions of other components are exactly the same as those in Example 1.

[0082] Comparative Example 5

[0083] This comparative example provides a high-voltage resistant electrolyte, which is different from Example 1 in that the mass fraction of 1,3-propane sultone is adjusted to 1wt%, and the contents and proportions of other components are exactly the same as those in Example 1.

[0084] Comparative Example 6

[0085] This comparative example provides a high-voltage resistant electrolyte, which is different from Example 1 in that the mass fraction of 1,3-propane sultone is adjusted to 3wt%, and the contents and proportions of other components are exactly the same as those in Example 1.

[0086] Comparative Example 7

[0087] This comparative example provides a high-voltage resistant electrolyte, which differs from Example 1 in that sodium nitrate is omitted, and the contents and proportions of other components are exactly the same as those in Example 1.

[0088] Comparative Example 8

[0089] This comparative example provides a high-voltage resistant electrolyte, which is different from Example 1 in that sodium difluorooxalatoborate is omitted, and the contents and proportions of other components are exactly the same as those in Example 1.

[0090] Comparative Example 9

[0091] This comparative example provides a high-voltage resistant electrolyte, which differs from Example 1 in that tris(trimethylsilyl)phosphite is omitted, and the contents and proportions of other components are exactly the same as those in Example 1.

[0092] Comparative Example 10

[0093] This comparative example provides a high-voltage resistant electrolyte, which differs from Example 1 in that vinylene carbonate is omitted, and the contents and proportions of other components are exactly the same as those in Example 1.

[0094] Comparative Example 11

[0095] This comparative example provides a high-voltage resistant electrolyte, which differs from Example 1 in that fluoroethylene carbonate is omitted, and the contents and proportions of other components are exactly the same as those in Example 1.

[0096] Comparative Example 12

[0097] This comparative example provides a high-voltage resistant electrolyte, which differs from Example 1 in that 1,3-propane sultone is omitted, and the contents and proportions of other components are exactly the same as those in Example 1.

[0098] Comparative Example 13

[0099] This comparative example provides a high-voltage resistant electrolyte, which is different from Example 1 in that sodium nitrate, sodium difluorooxalatoborate, tris(trimethylsilyl)phosphite, vinylene carbonate, fluoroethylene carbonate and 1,3-propane sultone are omitted, and the contents and proportions of other components are exactly the same as those in Example 1.

[0100] The button-type batteries were assembled using the high-voltage electrolyte provided in Examples 1-5 and Comparative Examples 1-13. The specific steps are as follows:

[0101] (1) Preparation of positive electrode sheet: Sodium vanadium phosphate, conductive agent acetylene black and binder PVDF were mixed in a mass ratio of 8:1:1, mixed and stirred in a certain amount of N-methylpyrrolidone solvent to prepare positive electrode active slurry; the positive electrode active slurry was evenly coated on the surface of aluminum foil, and the coating surface density was about 2.83 mg / cm 2 ; Then, the coated electrode was placed in a vacuum drying oven and dried at 80°C for 6 hours, then taken out and rolled with a roller press at a pressure of 10MPa, and finally a round positive electrode with a diameter of 14mm was prepared with a punching die;

[0102] (2) Preparation of negative electrode sheet: Hard carbon, conductive agent acetylene black and binder PVDF were mixed in a mass ratio of 8:1:1, mixed and stirred in a certain amount of N-methylpyrrolidone solvent to prepare a negative electrode active slurry; the negative electrode active slurry was evenly coated on the surface of aluminum foil, and the coating surface density was about 2.83 mg / cm 2 ; Then, the coated electrode was placed in a vacuum drying oven and dried at 80°C for 6 hours, then taken out and rolled with a roller press at a pressure of 10MPa, and finally a round negative electrode with a diameter of 14mm was prepared with a punching die;

[0103] (3) Battery assembly: In a glove box, the positive electrode sheet, glass fiber separator and negative electrode sheet prepared above are stacked in sequence and placed in a housing. The high-voltage electrolyte provided in Examples 1-5 of the present invention and Comparative Examples 1-13 are injected into the housing to assemble button cells. The entire assembly process is carried out in a glove box with an argon atmosphere.

[0104] The electrochemical performance test of the assembled button cell is carried out. The specific test steps are as follows:

[0105] (1) Constant current charge and discharge test (GCD)

[0106] The assembled button cells were charged and discharged at a constant current using the BluePower battery test system CT2001A to test the rate performance and cycle performance of the button cells.

[0107] (1.1) Rate performance

[0108] The button cells assembled from Example 1 and Comparative Example 7 were subjected to rate performance tests at room temperature (25°C), with a test voltage window of 2.5-4V and test current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, 5C and 10C, respectively. The discharge specific capacities of the button cells at different current densities were tested, and the results were as follows: Figure 1 As shown in the rate performance test diagram, it can be seen from the figure that the discharge specific capacity of the button battery assembled in Example 1 at a current rate of 0.1C is 117.4mAh / g, which is much higher than the discharge specific capacity of Comparative Example 7.

[0109] As the current density gradually increases from 0.1C to 10C, the discharge specific capacity of the button battery assembled in Example 1 is 117.4mAh / g, 116.8mAh / g, 115.6mAh / g, 115.3mAh / g, 112.5mAh / g, 108.1mAh / g or 104.9mAh / g, respectively. When the current density returns to 0.1C again, the discharge specific capacity of the button battery assembled in Example 1 recovers to 113.2mAh / g, which can reach 96.4% of the initial capacity (117.4mAh / g), which indicates that the button battery assembled in Example 1 has excellent rate performance.

[0110] As the current density gradually increases from 0.1C to 10C, the first-cycle discharge specific capacity of the button battery assembled in Comparative Example 7 is 97.3mAh / g, 92.7mAh / g, 90.6mAh / g, 86.4mAh / g, 81.5mAh / g, 48.7mAh / g, and 23.1mAh / g, respectively. When the current density returns to 0.1C again, the discharge specific capacity of the button battery assembled in Example 1 recovers to 90.2mAh / g, which can only reach 92.7% of the initial capacity.

[0111] (1.2) Cyclic performance test

[0112] The cycle capacity retention rate of the button cells assembled in Examples 1-5 and Comparative Examples 1-13 was tested. In a 25°C constant temperature box, the button cells were charged to 3.9V at a constant current of 0.2C, left for 5 minutes, and then discharged to 2V at a constant current, left for 5 minutes, and cycled 3 times to complete the pretreatment; the pretreated button cells were charged to 3.9V at a constant current of 0.1C, left for 5 minutes, and then discharged to 2V at a constant current, and the first cycle discharge capacity C1 was recorded, followed by leaving for 5 minutes, and then continued to charge to 3.9V at a constant current of 0.1C, left for 5 minutes, and then discharged to 2V at a constant current. After this charge and discharge process was cycled 500 times, the 500th discharge capacity C2 was recorded, and the capacity retention rate of the button cell was calculated according to the following formula:

[0113] Capacity retention rate (%) = (C2 / C1) × 100%.

[0114] In each group of embodiments (comparative examples), 10 groups of button batteries were tested and the average value was taken. The calculation results are shown in Table 1.

[0115] (2) Cyclic voltammetry (CV)

[0116] Cyclic voltammetry (CV) is a common electrochemical analysis method, which is mainly used to study the electrode reaction process and reversibility. The present invention uses an electrochemical workstation to perform CV test on the assembled button cell, with a test temperature of 25°C, a scan rate of 0.5mV / s, and a test voltage range of 0.0~2.0V.

[0117] After testing, we get Figure 2 The first cycle cyclic voltammetry curve (CV curve) is shown in the figure. It can be seen from the figure that a reduction peak below 0.1V appears in the CV curve, corresponding to Na + The voltage gap (ΔV) between the reduction peak and the oxidation peak reflects the Na + The kinetic behavior of embedding / ejection, the ΔV of the button cell assembled in Example 1 is 172 mV, which is much smaller than the ΔV (218 mV) of the button cell assembled in Comparative Example 13. This indicates that the high-voltage resistant electrolyte provided by the present invention can form a stable, uniform and dense SEI film on the electrode surface, thereby effectively improving the kinetic process of the electrode.

[0118] (3) Electrochemical impedance spectroscopy (EIS)

[0119] Electrochemical impedance spectroscopy (EIS) is a commonly used method for analyzing electrode process dynamics. The present invention uses an electrochemical workstation to perform EIS tests on button cells before and after cycling, performs fitting analysis on the impedance changes of button cells during cycling, and then analyzes the stability of button cells during cycling. The test temperature is 25°C, the polarization voltage is 5mV, and the frequency range is 0.01~100kHz.

[0120] The button cells assembled with the high-voltage electrolyte provided in Example 1 and Comparative Example 13 were subjected to impedance testing, and the EIS results were fitted with an equivalent circuit, where R SEI Represents the resistance of sodium ions passing through the SEI membrane. After testing, the following results are obtained: Figure 3 and Figure 4 The electrochemical impedance spectroscopy diagram is shown in Figure 3 The electrochemical impedance diagrams of the button-type battery assembled with the high-voltage electrolyte provided in Example 1 after the 5th, 10th, 25th and 50th cycles are shown in FIG. Figure 4 Electrochemical impedance diagrams of the button-type batteries assembled with the high-voltage resistant electrolyte provided in Comparative Example 13 after the 5th, 10th, 25th and 50th cycles.

[0121] Depend on Figure 3 It can be seen that the R of the button cell assembled in Example 1 is SEI As the number of cycles increases, there is almost no change. The R after the 5th, 10th, 25th, and 50th cycles is SEIThey are 3.0Ω, 3.1Ω, 3.4Ω, and 3.5Ω respectively. Figure 4 It can be seen that the R SEI As the number of cycles increases, the R value increases gradually. After the 5th, 10th, 25th, and 50th cycles, SEI They are 1.7Ω, 2.0Ω, 50.1Ω and 92.0Ω respectively.

[0122] This shows that the SEI film formed by the high-voltage resistant electrolyte provided in Example 1 has excellent structural stability and can effectively prevent the electrolyte from being further reduced on the surface of the hard carbon negative electrode. Therefore, as the number of cycles increases, the impedance of the button battery remains almost unchanged. However, the SEI film formed by the high-voltage resistant electrolyte provided in Comparative Example 13 will rupture during the cycle, resulting in a continuous increase in the thickness of the SEI film. As the number of cycles increases, the impedance of the button battery gradually increases.

[0123] The same test method was used to perform impedance tests on button cells assembled with the high-voltage electrolyte provided in Examples 1-5 and Comparative Examples 1-13, and the EIS results were fitted with an equivalent circuit to obtain R SEI , the results are shown in Table 1.

[0124] Table 1

[0125]

[0126] It can be seen from the test data provided in Examples 1-5 that the sodium ion battery assembled using the high-voltage resistant electrolyte provided by the present invention has excellent rate performance and cycle performance.

[0127] It can be seen from the test data provided by Example 1, Comparative Example 1 and Comparative Example 2 that excessively high or low addition amount of vinylene carbonate will affect the electrochemical performance of the sodium ion battery.

[0128] It can be seen from the test data provided by Example 1, Comparative Example 3 and Comparative Example 4 that excessively high or low addition amount of fluoroethylene carbonate will affect the electrochemical performance of the sodium ion battery.

[0129] It can be seen from the test data provided by Example 1, Comparative Example 5 and Comparative Example 6 that excessively high or low addition amount of 1,3-propane sultone will affect the electrochemical performance of the sodium ion battery.

[0130] It can be seen from the test data provided in Example 1 and Comparative Examples 7-13 that the present invention can significantly improve the electrochemical properties of sodium ion batteries by adding sodium nitrate, sodium difluorooxalatoborate, tris(trimethylsilyl)phosphite, vinylene carbonate, fluoroethylene carbonate and 1,3-propane sultone to the high-voltage resistant electrolyte.

[0131] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A high voltage resistant electrolyte, characterized in that: The high-voltage electrolyte comprises a conductive sodium salt, an organic solvent and a composite additive; wherein the conductive sodium salt is sodium hexafluorophosphate, the organic solvent is diethylene glycol dimethyl ether, and the composite additive is sodium nitrate, sodium difluorooxalatoborate, tris(trimethylsilyl)phosphite, vinylene carbonate, fluoroethylene carbonate and 1,3-propane sultone; The mass fraction of vinylene carbonate in the high-voltage electrolyte is 2.5 to 3.5 wt %; The mass fraction of fluoroethylene carbonate in the high-voltage electrolyte is 4.5-5.5wt%; The mass fraction of 1,3-propane sultone in the high-voltage electrolyte is 1.5-2.5 wt %.

2. The high voltage resistant electrolyte according to claim 1, characterized in that: The concentration of sodium hexafluorophosphate in the high-voltage electrolyte is 0.8-1.2 mol / L.

3. The high voltage resistant electrolyte according to claim 1, characterized in that: The molar concentration of sodium nitrate in the high-voltage electrolyte is 0.08-0.12 mol / L.

4. The high voltage resistant electrolyte according to claim 1, characterized in that: The mass fraction of sodium difluorooxalatoborate in the high-voltage electrolyte is 0.4-0.6 wt %.

5. The high voltage resistant electrolyte according to claim 1, characterized in that: The mass fraction of tris(trimethylsilyl)phosphite in the high-voltage electrolyte is 0.5-1.5 wt %.

6. A method for preparing a high voltage resistant electrolyte according to any one of claims 1 to 5, characterized in that: The preparation method comprises: In a glove box with an argon atmosphere, sodium nitrate, sodium difluorooxalatoborate, tris(trimethylsilyl)phosphite, vinylene carbonate, fluoroethylene carbonate and 1,3-propane sultone are added to diethylene glycol dimethyl ether and mixed evenly, and then molecular sieves are added to remove water and purify to obtain a mixed solution; sodium hexafluorophosphate is added to the mixed solution, and the high-voltage resistant electrolyte is obtained after mixing evenly.

7. A sodium ion battery comprising the high voltage resistant electrolyte according to any one of claims 1 to 5, characterized in that: The sodium ion battery comprises a shell and a battery core located inside the shell, the shell is injected with the high-voltage resistant electrolyte, the battery core is immersed in the high-voltage resistant electrolyte, and the battery core comprises a positive electrode sheet, a separator and a negative electrode sheet stacked in sequence; The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, a conductive agent and a binder, and the positive electrode active material is sodium vanadium phosphate; The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector. The negative electrode active material layer comprises a negative electrode active material, a conductive agent and a binder. The negative electrode active material is hard carbon.

Citation Information

Patent Citations

  • Sodium-ion battery electrolyte, sodium-ion battery and electric equipment

    CN118231761A

  • Sodium-ion battery electrolyte and sodium-ion battery containing same

    CN118281318A